2022
DOI: 10.1002/prp2.998
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological hypothesis: A recombinant probiotic for taming bacterial β‐glucuronidase in drug‐induced enteropathy

Abstract: Advances in pharmacomicrobiomics have shed light on the pathophysiology of drug‐induced enteropathy associated with the therapeutic use of certain non‐steroidal anti‐inflammatory drugs, anticancer chemotherapies and immunosuppressants. The toxicity pathway results from the post‐glucuronidation release and digestive accumulation of an aglycone generated in the context of intestinal dysbiosis characterized by the expansion of β‐glucuronidase‐expressing bacteria. The active aglycone could trigger direct or indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This is the most frequently observed mechanism leading to the gastrointestinal side effects caused by certain non-steroidal anti-inflammatory drugs (like diclofenac or indomethacin) or chemotherapy drugs (such as regorafenib or irinotecan). It involves enterohepatic recirculation and the enzymatic activity of gut microbiome β-glucuronidase overgrowth [55]. In another recent study by Bhatt et al, it was demonstrated that pharmacological intervention on the bacterial β-glucuronidase species proved to be helpful for irinotecan tolerance by reducing the gastrointestinal toxic side effects.…”
Section: Gastrointestinal Microbiome Estrobolome and Bacterial Specie...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is the most frequently observed mechanism leading to the gastrointestinal side effects caused by certain non-steroidal anti-inflammatory drugs (like diclofenac or indomethacin) or chemotherapy drugs (such as regorafenib or irinotecan). It involves enterohepatic recirculation and the enzymatic activity of gut microbiome β-glucuronidase overgrowth [55]. In another recent study by Bhatt et al, it was demonstrated that pharmacological intervention on the bacterial β-glucuronidase species proved to be helpful for irinotecan tolerance by reducing the gastrointestinal toxic side effects.…”
Section: Gastrointestinal Microbiome Estrobolome and Bacterial Specie...mentioning
confidence: 99%
“…The GUS may represent a modifiable factor. Additionally, the inhibition of the enzymatic activity of such species could contribute to better chemotherapy outcomes with fewer adverse effects, thereby affecting the efficacy and adherence to such treatment in pancreatic or colorectal cancer patients [55,56].…”
Section: Gastrointestinal Microbiome Estrobolome and Bacterial Specie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics colonize and regulate the unbalanced microflora of the host, directly acting on host epithelial and immune cells and regulating the epithelial or immune cells of specific tissues of the host through their metabolites in situ or by entering the circulation and remodeling the microenvironment of the lesion site ( 2 ). Unlike drugs, probiotics are associated with less side-effects, such as intestinal ecological disorder and immune dysfunction ( 3 ). Various forms of probiotic preparations are available.…”
Section: Introductionmentioning
confidence: 99%